2011
DOI: 10.4236/jep.2011.25074
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Tolerance to High Concentrations of Carbon Dioxide: A Review

Abstract: The increasing concentration of carbon dioxide (CO<sub>2</sub>) in the atmosphere is considered to be one of the main causes of the global warming problem. Moreover, there is an international movement to reduce the emission of CO<sub>2</sub> by imposing different measures such as carbon tax. Biological CO<sub>2</sub> fixation has been extensively investigated as part of efforts to solve the global warming problem. Microalgae are fast growing systems that can consume high qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 45 publications
0
51
0
3
Order By: Relevance
“…Alguns pesquisadores relatam que espécies de microalgas nativas podem ser mais tolerantes a condições locais, apresentando maiores taxas fotossintéticas (Radmann et al, 2011;Salih, 2011). O isolamento de microalgas provenientes da região pode maximizar a eficiência destes microorganismos em biofixar CO 2 .…”
Section: Introductionunclassified
“…Alguns pesquisadores relatam que espécies de microalgas nativas podem ser mais tolerantes a condições locais, apresentando maiores taxas fotossintéticas (Radmann et al, 2011;Salih, 2011). O isolamento de microalgas provenientes da região pode maximizar a eficiência destes microorganismos em biofixar CO 2 .…”
Section: Introductionunclassified
“…The duration of this phase depends on the initial inoculum concentration, the pre-cultivation time and the physiological state of the microorganism. Native species of microalgae are more tolerant of local conditions and exhibit higher rates of photosynthesis and biomass production (Salih 2011). The environmental impact of the high concentrations of solid residues produced by burning the fossil fuels on such strains would be reduced compared with that on native microorganisms, eliminating the need to look for tolerant strains.…”
mentioning
confidence: 99%
“…In terms of carbon capture and storage, various studies have been done to showcase the ability of carbon fixation by microalgae, which showed better results compared to plants due to its higher growth rate [3]. After all, both microalgae and plants capture and fix CO 2 through natural photosynthesis process.…”
Section: Introductionmentioning
confidence: 99%